Antimicrobial Peptides: The Game-Changer in the Epic Battle Against Multidrug-Resistant Bacteria - Helal F. Hetta; Nizar Sirag; Shumukh M. Alsharif; Ahmad A. Alharbi; Tala T. Alkindy; Alanoud Alkhamali; Abdullah S. Albalawi; Yasmin N. Ramadan; Zainab I. Rashed; Fawaz E. Alanazi (Pharmaceuticals)
The rapid progress of antibiotic resistance among bacteria has prompted serious medical concerns regarding how to manage multidrug-resistant (MDR) bacterial infections. One emerging strategy to combat antibiotic resistance is the use of antimicrobial peptides (AMPs), which are amino acid chains that act as broad-spectrum antimicrobial molecules and are essential parts of the innate immune system in mammals, fungi, and plants. AMPs have unique antibacterial mechanisms that offer benefits over conventional antibiotics in combating drug-resistant bacterial infections. Currently, scientists have conducted multiple studies on AMPs for combating drug-resistant bacterial infections and found that AMPs are a promising alternative to conventional antibiotics. On the other hand, bacteria can develop several tactics to resist and bypass the effect of AMPs. Therefore, it is like a battle between the bacterial community and the AMPs, but who will win? This review provides thorough insights into the development of antibiotic resistance as well as detailed information about AMPs in terms of their history and classification. Furthermore, it addresses the unique antibacterial mechanisms of action of AMPs, how bacteria resist these mechanisms, and how to ensure AMPs win this battle. Finally, it provides updated information about FDA-approved AMPs and those that were still in clinical trials. This review provides vital information for researchers for the development and therapeutic application of novel AMPs for drug-resistant bacterial infections.